Análisis espacial del uso de suelo en el cantón Vinces, provincia de los Ríos a partir de las imágenes landsat 8 - Peralta Vera, Haylis Thalya (2018)
The Tasseled Cap Spectral Transformation (TTC) of the Landsat 8 images of the last generation satellite was carried out in the present research project, which allowed to obtain the three components such as Brightness, which reflects the changes in the reflectivity of the image, the Greenery that is the component that best indicates the vegetation cover, and the Humidity which shows the water content in both the vegetation and the soil. These satellite images were analyzed for the canton of Vinces for two different seasons (winter and summer). The accuracy of the land use maps for each date was evaluated using the confusion matrix and the kappa coefficient, observing the satisfactory coincidence between both classifications of land use with the reference data obtained in the field and in Google Earth. An accuracy of 88.33% was achieved in the month of January and 86.67% in the month of September 2015. From the confusion matrix, a kappa coefficient of 75% was found in January and 77% in September, verifying the good quality of the results obtained. The analysis of the variance detected that there are no statistically significant differences in the components of brightness and humidity, while in the verdure component it was detected that there is a statistically significant difference between the two supervised classifications of the images corresponding to winter and summer. The comparative analysis of the two supervised classifications of the images corresponding to winter and summer allowed observing that the bodies of water in winter have an area of 74.77 km2 while in summer it falls to 41.19 km2. The short cycle crops increase to 1268.42 km2 in winter and in summer there is an area of 1064.66 km2. The coverage of other types of vegetation have an area of 282.7 km2 in winter, decreasing to 149.84 km2 in summer, due to the fact that in winter greater coverage is reflected in the forests and vegetation that grow at this time. The Urban area is the coverage with the highest rate of change from 124.51 km2 to 18.47 km2. The bare ground in the winter image is 17.84 km2 while in the summer it increases to 322.82 km2. It was verified that the Landsat images allow to detect the regional patterns of land use and conditions in Ecuador, especially in vegetation and water body coverings. In spite of having difficulties in obtaining clean images due to the climatic conditions of the area, the TTC gives good results for both seasons of the year. It is recommended that the applied methodology be used by sectional governments, in territorial planning processes. Keywords: Land Uses, Landsat Images, Spectral Transformations, Supervised Classification.